Adult Presentation of Untreated Exstrophy–Epispadias Complex with Squamous Cell Carcinoma: A Rare Case Report - Amin, Md Ruhul; Islam, Md Nazrul; Chowdhury , Pravin (Journal of Paediatric Surgeons of Bangladesh, 2026)
Exstrophy–epispadias complex (EEC) is a rare congenital anomaly characterized by a midline defect of the lower abdominal wall involving the urinary bladder, external genitalia, and pelvic bones. Early diagnosis and surgical reconstruction in the neonatal period is the standard of care. Untreated cases persisting into adulthood are extremely uncommon and are associated with a significant risk of malignant transformation of the exposed bladder mucosa. We report a rare case of untreated exstrophy–epispadias complex in a 38-year-old male who presented with an ulcerated bladder plate that was subsequently diagnosed as invasive squamous cell carcinoma. The patient underwent organ-sparing radical cystectomy with continent urinary diversion using an ileocecal segment and a Mitrofanoffcatheterizable channel, along with epispadias repair and umbilicoplasty. Histopathology confirmed grade II invasive squamous cell carcinoma with tumor-free surgical margins. This case highlights the importance of early diagnosis and treatment of bladder exstrophy and demonstrates the potential for malignant transformation in long-standing untreated cases. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 49-51